2018
DOI: 10.1159/000481143
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Iron Carboxymaltose May Have an Effect on Haemoglobin Levels in Cardiothoracic Surgical Patients on the ICU - an Observational Pilot Study about Anaemia Treatment with Intravenous Iron

Abstract: Background: Post-operative anaemia is associated with increased morbidity and mortality. Positive effects of post-operative intravenous iron (IVI) after elective orthopaedic, abdominal and genitourinary surgery have been reported. The current observational trial investigated the prevalence of post-operative anaemia, the effect of IVI on haemoglobin levels, the use of blood transfusions and diagnoses related to infections. Methods: 1,265 patients on five ICUs of Münster University Hospital were screened for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…were RCTs (32 920 participants) and 8 were NRSs (7146 participants). [185][186][187][188][189][190][191][192] of bias assessments, of NRSs that reported on outcomes of infection is provided in eAppendix 2 and eTables 3 and 4 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…were RCTs (32 920 participants) and 8 were NRSs (7146 participants). [185][186][187][188][189][190][191][192] of bias assessments, of NRSs that reported on outcomes of infection is provided in eAppendix 2 and eTables 3 and 4 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…were RCTs (32 920 participants) and 8 were NRSs (7146 participants). [185][186][187][188][189][190][191][192] Two RCTs 47,106 were analyzed as 2 separate studies each. A descriptive summary, including study characteristics and risk of bias assessments, of NRSs that reported on outcomes of infection is provided in eAppendix 2 and eTables 3 and 4 in the Supplement.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There is a paucity of studies that treat preoperative iron-deficiency anemia with just iron. One prospective observational study demonstrated an increased hemoglobin level in pretreated anemic patients, 9 but a small RCT of only 50 patients did not. 10 Therefore, it is difficult to confidently state that the direct treatment of iron-deficiency anemia before cardiac surgery with iron alone will result in improved outcomes, but it is clear that the treatment of anemia is warranted in the elective surgical patient.…”
Section: Risk Assessment For Treatment Of Anemiamentioning
confidence: 99%